The Influence of the Free Curriculum and Technology-based Learning Media on Digital Literacy - Nasori, Ahmad; Aslindar, Dwiastarani; Puspasari, Elsa (Jurnal Simki Pedagogia, 2024)
The aim of this research is to understand the influence of the Free Curriculum and Technology-based Learning Media on Digital Literacy. This research is quantitative research with the type of research used in this research is associative research. On data analysis using double linear regression analysis tests and t tests then continued with f tests and desimination tests. The results of the study show that digital literacy has a very good category. In the application of the Free Curriculum is included in the good category and the use of technology-based learning media is in the excellent category. based on the results of a double regression analysis on the simultaneous test between the independent curriculum and the technologically based learning media jointly influenced on digital literature with a F value of 76,752 and a significance value of 0,000.